The Macmillan Reader: Instructors Manual - Nadell, Judith (New York Macmillan Publishing Company, 1987)
One way of enjoying teaching is to get together and share ideas and problems, as well as talk about the good times. This manual is full of thoughts about teaching composition. Even if you do not agree with everything written in this book, you may at least find a new way of viewing something.
Keywords: Writing